PENGGUNAAN MEDIA YOUTUBE SEBAGAI BAHAN AJAR BERCERITA ULANG UNTUK MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK KELAS IV SDN 2 BOJONG LELES LEBAK BANTEN - Saroh, Siti; Yuliawati, Yuliawati; Tisnasari, Sundawati (PREDIKSI (PROFESI PENDIDIKAN INDONESIA), 2024)
The problem of learning motivation of fourth grade students at SDN 2 Bojong Leles became the basis for conducting this class action research (CAR). The purpose of this Class Action Reseach is to increase students' learning motivation by applying the use of YouTube media. The use of YouTube media can create a more meaningful learning process where students experience learning using audio-visual media. The subjects of this study were fourth grade students at SDN 2 Bojong Leles, totaling 43 students. This research was conducted in 2 cycles with four stages in each cycle, namely planning, action, observation and reflection. Data collection methods used are the method of documentation, observation, interviews and tests. The data obtained in this study are quantitative data and qualitative data. The results showed that the first cycle was 60% at the first meeting and increased to 65% at the second meeting, so that the average percentage value for cycle I was 62.5%. In cycle II, it obtained a percentage value of 75% at the first meeting and increased at the second meeting, namely to 80% so that the average percentage value for cycle II was 77.5%. Based on these results, it can be concluded that the use of YouTube media can increase learning motivation in class IV students at SDN 2 Bojong Leles. Keywords: Use of Youtube Media, Learning Motivation